(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2026)
Indonesia is one of the countries with a high level of disaster risk, making disaster mitigation information essential for improving community preparedness. However, access to disaster mitigation information is often limited by the need to access specific platforms or applications. This study aims to develop a WhatsApp-based disaster mitigation chatbot using n8n workflow automation and an AI Agent to provide disaster mitigation information automatically and interactively. The research employed a prototype development method consisting of requirements identification, rapid planning, prototype design, implementation, testing, and refinement. The developed system integrates WhatsApp as a communication platform, n8n as a workflow automation tool, and an AI Agent equipped with disaster mitigation knowledge domains. Functional testing results indicate that all main system functions operated successfully, including message reception, question processing, response generation, and response delivery. Response testing also showed that the chatbot was able to provide relevant information within the predefined disaster mitigation domains while rejecting questions outside the specified knowledge boundary. The results demonstrate that the proposed chatbot can serve as an accessible and responsive disaster mitigation education medium through a widely used communication platform. Future development may focus on integrating real-time disaster data and early warning notification features.